Long-term memory plasticity in a decade-long connectivity study post anterior temporal lobe resection - Marine N. Fleury; Lawrence P. Binding; Peter Taylor; Fenglai Xiao; Davide Giampiccolo; Sarah Buck; Gavin P. Winston; Pamela J. Thompson; Sallie Baxendale; Andrew W. McEvoy; Matthias J. Koepp; John S. Duncan; et al. (Nature Communications)
Abstract Approximately 40% of individuals undergoing anterior temporal lobe resection for temporal lobe epilepsy experience episodic memory decline. There has been a focus on early memory network changes; longer-term plasticity and its impact on memory function are unclear. Our study investigates neural mechanisms of memory recovery and network plasticity over nearly a decade post-surgery. We assess memory network changes, from 3–12 months to 10 years postoperatively, in 25 patients (12 left-sided resections) relative to 10 healthy matched controls, using longitudinal task-based functional MRI and standard neuropsychology assessments. We observe key adaptive changes in memory networks of a predominantly seizure-free cohort. Ongoing neuroplasticity in posterior medial temporal regions and contralesional cingulum or pallidum contribute to long-term verbal and visual memory recovery. Here, we show the potential for sustained cognitive improvement and importance of strategic approaches in epilepsy treatment, advocating for conservative surgeries and long-term use of cognitive rehabilitation for ongoing recovery.